2016
DOI: 10.1021/acs.est.6b02284
|View full text |Cite
|
Sign up to set email alerts
|

Structure, Variation, and Co-occurrence of Soil Microbial Communities in Abandoned Sites of a Rare Earth Elements Mine

Abstract: Mining activity for rare earth elements (REEs) has caused serious environmental pollution, particularly for soil ecosystems. However, the effects of REEs on soil microbiota are still poorly understood. In this study, soils were collected from abandoned sites of a REEs mine, and the structure, diversity, and co-occurrence patterns of soil microbiota were evaluated by Illumina high-throughput sequencing targeting 16S rRNA genes. Although microbiota developed significantly along with the natural restoration, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
57
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(75 citation statements)
references
References 77 publications
10
57
3
Order By: Relevance
“…The sensitivity of the response of a microbial community, specifically bacterial and fungal communities, reflects a change in soil quality [ 32 , 33 ]. For instance, a significant alteration of microbial community in IAC mining wasteland was demonstrated in our previous study [ 34 ] and some other reports [ 35 , 36 , 37 ]. In this study, we used sludge biochar as a soil ameliorant and alfalfa as the revegetation plant and conducted pot trials in a climate-controlled chamber, and we test the hypothesis that sludge biochar amendment and alfalfa plantation can ameliorate physicochemical properties and increase the microbial diversity of soil from IAC mining wastelands.…”
Section: Introductionmentioning
confidence: 51%
“…The sensitivity of the response of a microbial community, specifically bacterial and fungal communities, reflects a change in soil quality [ 32 , 33 ]. For instance, a significant alteration of microbial community in IAC mining wasteland was demonstrated in our previous study [ 34 ] and some other reports [ 35 , 36 , 37 ]. In this study, we used sludge biochar as a soil ameliorant and alfalfa as the revegetation plant and conducted pot trials in a climate-controlled chamber, and we test the hypothesis that sludge biochar amendment and alfalfa plantation can ameliorate physicochemical properties and increase the microbial diversity of soil from IAC mining wastelands.…”
Section: Introductionmentioning
confidence: 51%
“…( d ) Abundance (%) of bacterial communities in different type of sites at the phylum level. Active: active sites in present study; Aband: abandoned sites in present study; SA, slightly acidic sites22; Pb-Zn, an abandoned Pb-Zn mine 23 , REE: a rare Earth element mine 24 ; CA, Chlor-alkali sites 25 . The inset Table in Fig.…”
Section: Resultsmentioning
confidence: 76%
“…3d ). Results of ANOVA using the data from these sites (active, abandoned, and literature 21 , 24 also indicated that TP and Fe had significant differences ( p < 0.05, Fig. 3 ).…”
Section: Resultsmentioning
confidence: 78%
“…On the contrary, a better efficiency of the biological control agents is obtained when microbial consortia and not single strains are used to control pathogenic fungi in soils and substrates (Danon et al, 2010 ; Jain et al, 2012 ; Pertot et al, 2017 ). Thus, it is becoming clearer and clearer that soil functionality depends on the community pattern and that the activity of the microorganisms directly involved in the targeted function is only possible in the presence of the different components of this community, without these components being directly involved in the function of interest (Tyc et al, 2014 ; Williams et al, 2014 ; Chao et al, 2016 ). Therefore, an alternative strategy to identify the members of the microbial consortium responsible for soil suppressiveness would be to erode diversity by performing serial dilutions of the suppressive soil until it loses its suppressiveness.…”
Section: Discussionmentioning
confidence: 99%